Sodium ion positive electrode material active substance mixed with composite sodium ferric phosphate, positive electrode material and sodium ion battery

By mixing composite sodium iron phosphate (NFPP) with layered metal oxides, Prussian blue compounds and other materials, high-performance sodium ion battery positive electrode materials are prepared, which solves the thermal stability, processing performance and The problem of insufficient safety performance has achieved significant improvements in battery cell energy density, safety and circulation performance.

CN119481041APending Publication Date: 2025-02-18SHANGHAI PUNA ENERGY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411606300.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode materials have shortcomings in thermal stability, processing performance and safety performance, resulting in poor circulation and safety performance.

Method used

A high-performance sodium ion battery cathode material is prepared by adjusting the material ratio and adding conductive agents and binders.

Benefits of technology

It significantly improves the energy density, safety and circulation performance of the battery cell, and meets the market's requirements for high safety, high capacity and long circulation of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481041A_ABST
    Figure CN119481041A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion battery positive electrode material active substance mixed with composite sodium ferric phosphate, which is a mixture of composite sodium ferric phosphate (NFPP) and one or more of layered metal oxide, Prussian blue compounds and other polyanion materials, wherein the composite sodium ferric phosphate (NFPP) accounts for 5%-95% of the active substance of the sodium ion battery positive electrode material, and the other 95%-5% of the active substance is a material formed by mixing one or more of a layered metal oxide, a prussian blue compound and other polyanion materials. According to the sodium ion positive electrode material active substance mixed with the composite sodium ferric phosphate (NFPP), the positive electrode material and the sodium ion battery using the positive electrode material provided by the invention, the energy density, the safety and the cycle performance of a battery cell are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium ion batteries, and in particular to a mixed composite sodium iron phosphate positive electrode material active substance, a positive electrode material and a sodium ion battery using the same. Background Art

[0002] Sodium-ion batteries have the advantages of abundant resources, good safety, excellent high and low temperature performance, and low cost. They are currently widely valued in the fields of power and energy storage and have become the preferred next-generation new energy technology for power and energy storage. Continuously improving the processing performance, electrical performance, and safety performance of sodium-ion batteries has become an urgent research topic for sodium-ion batteries.

[0003] At present, the cathode materials of sodium ion batteries mainly include layered metal oxides, polyanion compounds and Prussian blue compounds. Among them, layered metal oxides and Prussian blue compounds have high specific capacity, but poor thermal stability and processing performance. The battery cells prepared from layered metal oxides and Prussian blue compounds have poor safety performance and cycle performance. Although the specific capacity of composite sodium iron phosphate (Na4Fe3P2O7(PO4)2 and derivatives, referred to as NFPP) in polyanion compounds is low, the raw materials do not contain precious metals, the cost is low, and the material is highly thermally stable. The battery cells prepared from composite sodium iron phosphate (NFPP) have excellent cycle performance and safety performance. Composite sodium iron phosphate (NFPP) is mixed with one or more positive electrodes of metal oxides, Prussian blue compounds and other polyanion compounds to prepare a positive electrode sheet, and then prepared into a sodium ion battery, which meets people's requirements for high capacity, high safety and long cycle performance of sodium ion batteries and promotes the further application of sodium ion batteries. Summary of the invention

[0004] The present invention aims to solve the above technical problems and proposes a sodium ion positive electrode material active material mixed with composite sodium iron phosphate, a positive electrode material and a sodium ion battery. The specific technical scheme is as follows:

[0005] A sodium ion battery positive electrode material active substance mixed with composite sodium iron phosphate. The sodium ion battery positive electrode material active substance is a mixture of composite sodium iron phosphate (NFPP) and one or more of layered metal oxides, Prussian blue compounds, and other polyanion materials, wherein the composite sodium iron phosphate (NFPP) accounts for 5% to 95% of the sodium ion battery positive electrode material active substance, and the other 95% to 5% is a material obtained by mixing one or more of layered metal oxides, Prussian blue compounds, and other polyanion materials.

[0006] A sodium ion battery positive electrode material mixed with composite sodium iron phosphate comprises the sodium ion battery positive electrode material active material, a conductive agent and a binder as described above; the sodium ion battery positive electrode material active material is 93% to 97%, the binder is 1.5% to 3.5%, and the conductive agent is 1% to 3.5%.

[0007] Preferably, the binder is polyvinylidene fluoride (PVDF); the conductive agent is any one of conductive carbon black (SP), conductive graphite, acetylene black, carbon nanotubes (CNTs), or a composite conductive agent mixed with any of the above.

[0008] Preferably, the solvent for preparing the sodium ion positive electrode material is N-methylpyrrolidone (NMP).

[0009] The present invention also provides a sodium ion battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode is a positive electrode sheet prepared from the aforementioned sodium ion positive electrode material.

[0010] Preferably, the sodium ion battery adopts a cylindrical cell, a soft-pack cell or a square-shell cell.

[0011] Preferably, the negative electrode is hard carbon.

[0012] Preferably, the electrolyte of the electrolyte is one or both of NaPF6 and NaFSI.

[0013] Among them, the general structural formula of layered transition metal oxides is NaxMO2 (M = Co, Mn, Fe, Cu, Cr, Ni, etc.); polyanionic compounds mainly include phosphate and sulfate systems, and the phosphate system is mainly iron-based and vanadium-based systems, among which the general structural formula of iron-based phosphate system is Na4Fe x P4O 12+x (2≤x≤4), where when X is close to 2, it is Na2FeP2O7 (abbreviated as NFPO), when X is close to 3, it is Na4Fe3(PO4)2P2O7 (abbreviated as NFPP), when X is close to 4, it is NaFePO4 (abbreviated as NFP), and sodium vanadium phosphate Na3V2(PO4)3. The sulfate system is mainly sodium iron sulfate with the general formula Na (2+2x) Fe x (SO4)2(0.5≤x≤1)(NFS for short); the chemical formula of Prussian cathode materials can be expressed as Na x M1[M2(CN)6](0<X<2), M1 is Fe, Mn or Ni, M2 is Fe or Mn, according to Na + The content is different, x < 1 is called Prussian blue, x ≥ 1 is called Prussian white.

[0014] The beneficial effects of the present invention are as follows: the sodium ion positive electrode material active substance mixed with composite sodium iron phosphate (NFPP), the positive electrode material and the sodium ion battery using the positive electrode material provided by the present invention significantly improve the energy density, safety and cycle performance of the battery cell, and the advantages of various materials are included to make up for the disadvantages of unilateral materials, meet the market requirements for high safety, high capacity and long cycle of sodium ion batteries, and are conducive to the widespread use of sodium ion batteries in power and energy storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] The drawings described herein are used to provide further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0016] Figure 1 It is a comparison chart of the cycle performance test of the soft-pack batteries prepared in Examples 1, 2, 3 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0017] In order to more clearly illustrate the overall concept of the present application, a detailed description is given below in an illustrative manner in conjunction with the accompanying drawings.

[0018] A positive electrode material mixed with composite sodium iron phosphate (NFPP), including an active substance, a conductive agent and a binder, wherein the active substance is a mixture of composite sodium iron phosphate (NFPP) and one or more of layered metal oxides, Prussian blue compounds, and other polyanion materials. Calculated by weight percentage, the active substance is 93% to 97%, the binder is 1.5% to 3.5%, and the conductive agent is 1% to 3.5%, wherein the composite sodium iron phosphate (NFPP) accounts for 5% to 95% of the active substance. In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail with reference to the embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0019] Example 1

[0020] The positive electrode active material is a mixed material of composite sodium iron phosphate (NFPP) and metal layered oxide with a mass ratio of 9.5:0.5.

[0021] (1) Weighing raw materials: weighing according to the ratio of active material to binder to conductive agent to account for 95%, 2.5%, and 2.5%, wherein the composite sodium iron phosphate (NFPP) accounts for 95% of the active material, the conductive agent is conductive carbon black (SP), carbon nanotubes (CNTs) or a combination thereof, the binder is polyvinylidene fluoride (PVDF), and the total weight of the powder is 8 kg.

[0022] (2) Preparation of adhesive solution: In an environment with humidity less than 10%, weigh 3298 g of solvent N-methylpyrrolidone (NMP) and add it to a stirring device, add 210.5 g of PVDF into the NMP and stir. The stirring device is kept in a vacuum state, the stirring revolution speed is 60 rpm, the dispersion speed is 3500 rpm, and the stirring time is 240 min to obtain PVDF adhesive solution.

[0023] (3) Preparation of conductive adhesive: SP and CNTs were added into PVDF adhesive solution, the stirring device was kept in vacuum state, the stirring revolution speed was 60 rpm, the dispersion speed was 3500 rpm, and the stirring time was 60 min to obtain PVDF adhesive solution.

[0024] (4) Preparation of slurry: The positive electrode active material is added to the conductive glue evenly three times and stirred. After scraping, the stirring equipment is kept in a vacuum state. The stirring revolution speed is 60 rpm, the dispersion speed is 4000 rpm, and the stirring time is 180 min. After adding solvent and stirring, the slurry viscosity is adjusted to 6000-8000 mPa.s and the fineness is less than 20 μm. After turning over to remove bubbles, it is coated.

[0025] (5) The obtained main material is coated on an aluminum foil with a thickness of 13 μm, and the NMP is removed by high-temperature drying in an oven. The mixed positive electrode sheet is obtained after rolling and die-cutting.

[0026] (6) Furthermore, the negative electrode active material hard carbon, SP, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) were dissolved in deionized water in a stirring device at a mass ratio of 94:1:2:3, stirred evenly to form a slurry, coated on a 12 μm aluminum foil, and dried. After rolling and die-cutting, a negative electrode sheet was obtained.

[0027] (7) Cell preparation: The positive electrode sheet and the negative electrode sheet are stacked to obtain a roll core, which is packaged with an aluminum-plastic film and then baked in a vacuum nitrogen exchange process. When the moisture content reaches below 300 pm, the electrolyte is injected to seal the roll core. After high-temperature immersion for 48 hours, pressurized formation, high-temperature aging, capacity distribution, and K value testing, a 20Ah soft-pack sodium-ion battery is obtained.

[0028] Example 2

[0029] The positive electrode active material is a mixed material of composite sodium iron phosphate (NFPP) and metal layered oxide with a mass ratio of 7:3.

[0030] (1) Weighing raw materials: weighing according to the ratio of 95% active material, 2.5% binder, and 2.5% conductive agent, wherein the composite sodium iron phosphate accounts for 70% of the active material, wherein the conductive agent is conductive carbon black (SP), carbon nanotubes (CNTs) or a combination thereof, and the binder is polyvinylidene fluoride (PVDF), and the total weight of the powder is 8 kg.

[0031] (2) Preparation of adhesive solution: In an environment with humidity less than 10%, weigh 3298 g of solvent N-methylpyrrolidone (NMP) and add it to a stirring device, add 210.5 g of PVDF into the NMP and stir. The stirring device is kept in a vacuum state, the stirring revolution speed is 60 rpm, the dispersion speed is 3500 rpm, and the stirring time is 240 min to obtain PVDF adhesive solution.

[0032] (3) Preparation of conductive adhesive: SP and CNTs were added into PVDF adhesive solution, the stirring device was kept in vacuum state, the stirring revolution speed was 60 rpm, the dispersion speed was 3500 rpm, and the stirring time was 60 min to obtain PVDF adhesive solution.

[0033] (4) Preparation of slurry: The positive electrode active material is added to the conductive glue evenly three times and stirred. After scraping, the stirring equipment is kept in a vacuum state. The stirring revolution speed is 60 rpm, the dispersion speed is 4000 rpm, and the stirring time is 180 min. After adding solvent and stirring, the slurry viscosity is adjusted to 6000-8000 mPa.s and the fineness is less than 20 μm. After turning over to remove bubbles, it is coated.

[0034] (5) The obtained main material is coated on an aluminum foil with a thickness of 13 μm, and the NMP is removed by high-temperature drying in an oven. The mixed positive electrode sheet is obtained after rolling and die-cutting.

[0035] (6) Furthermore, the negative electrode active material hard carbon, SP, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) were dissolved in deionized water in a stirring device at a mass ratio of 94:1:2:3, stirred evenly to form a slurry, coated on a 13 μm aluminum foil, and dried. After rolling and die-cutting, a negative electrode sheet was obtained.

[0036] (7) Cell preparation: The positive electrode sheet and the negative electrode sheet are stacked to obtain a roll core, which is packaged with an aluminum-plastic film and then baked in a vacuum nitrogen exchange process. When the moisture content reaches below 300 pm, the electrolyte is injected to seal the roll core. After high-temperature immersion for 48 hours, pressurized formation, high-temperature aging, capacity distribution, and K value testing, a 20Ah soft-pack sodium-ion battery is obtained.

[0037] Example 3

[0038] The positive electrode active material is a mixed material with a mass ratio of 1:1 between composite sodium iron phosphate (NFPP) and metal layered oxide.

[0039] (1) Weighing raw materials: weighing according to the ratio of 95% active material, 2.5% binder, and 2.5% conductive agent, wherein the composite sodium iron phosphate accounts for 50% of the active material, wherein the conductive agent is conductive carbon black (SP), carbon nanotubes (CNTs) or a combination thereof, and the binder is polyvinylidene fluoride (PVDF), and the total weight of the powder is 8 kg.

[0040] (2) Preparation of adhesive solution: In an environment with humidity less than 10%, weigh 3298 g of solvent N-methylpyrrolidone (NMP) and add it to a stirring device, add 210.5 g of PVDF into the NMP and stir. The stirring device is kept in a vacuum state, the stirring revolution speed is 60 rpm, the dispersion speed is 3500 rpm, and the stirring time is 240 min to obtain PVDF adhesive solution.

[0041] (3) Preparation of conductive adhesive: SP and CNTs were added into PVDF adhesive solution, the stirring device was kept in vacuum state, the stirring revolution speed was 60 rpm, the dispersion speed was 3500 rpm, and the stirring time was 60 min to obtain PVDF adhesive solution.

[0042] (4) Preparation of slurry: The positive electrode active material is added to the conductive glue evenly three times and stirred. After scraping, the stirring equipment is kept in a vacuum state. The stirring revolution speed is 60 rpm, the dispersion speed is 4000 rpm, and the stirring time is 180 min. After adding solvent and stirring, the slurry viscosity is adjusted to 6000-8000 mPa.s and the fineness is less than 20 μm. After turning over to remove bubbles, it is coated.

[0043] (5) The obtained main material is coated on an aluminum foil with a thickness of 13 μm, and the NMP is removed by high-temperature drying in an oven. The mixed positive electrode sheet is obtained after rolling and die-cutting.

[0044] (6) Furthermore, the negative electrode active material hard carbon, SP, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) were dissolved in deionized water in a stirring device at a mass ratio of 94:1:2:3, stirred evenly to form a slurry, coated on a 13 μm aluminum foil, and dried. After rolling and die-cutting, a negative electrode sheet was obtained.

[0045] (7) Cell preparation: The positive electrode sheet and the negative electrode sheet are stacked to obtain a roll core, which is packaged with an aluminum-plastic film and then baked in a vacuum nitrogen exchange process. When the moisture content reaches below 300 pm, the electrolyte is injected to seal the roll core. After high-temperature immersion for 48 hours, pressurized formation, high-temperature aging, capacity distribution, and K value testing, a 20Ah soft-pack sodium-ion battery is obtained.

[0046] Example 4

[0047] The positive electrode active material is a mixed material of composite sodium iron phosphate (NFPP) and metal layered oxide with a mass ratio of 3:7.

[0048] (1) Weighing raw materials: weighing according to the ratio of active material to binder to conductive agent to account for 95%, 2.5%, and 2.5%, wherein the composite sodium iron phosphate accounts for 30% of the active material, wherein the conductive agent is conductive carbon black (SP), carbon nanotubes (CNTs) or a combination thereof, and the binder is polyvinylidene fluoride (PVDF), and the total weight of the powder is 8 kg.

[0049] (2) Preparation of adhesive solution: In an environment with humidity less than 10%, weigh 3298 g of solvent N-methylpyrrolidone (NMP) and add it to a stirring device, add 210.5 g of PVDF into the NMP and stir. The stirring device is kept in a vacuum state, the stirring revolution speed is 60 rpm, the dispersion speed is 3500 rpm, and the stirring time is 240 min to obtain PVDF adhesive solution.

[0050] (3) Preparation of conductive adhesive: SP and CNTs were added into PVDF adhesive solution, the stirring device was kept in vacuum state, the stirring revolution speed was 60 rpm, the dispersion speed was 3500 rpm, and the stirring time was 60 min to obtain PVDF adhesive solution.

[0051] (4) Preparation of slurry: The positive electrode active material is added to the conductive glue evenly three times and stirred. After scraping, the stirring equipment is kept in a vacuum state. The stirring revolution speed is 60 rpm, the dispersion speed is 4000 rpm, and the stirring time is 180 min. After adding solvent and stirring, the slurry viscosity is adjusted to 6000-8000 mPa.s and the fineness is less than 20 μm. After turning over to remove bubbles, it is coated.

[0052] (5) The obtained main material is coated on an aluminum foil with a thickness of 13 μm, and the NMP is removed by high-temperature drying in an oven. The mixed positive electrode sheet is obtained after rolling and die-cutting.

[0053] (6) Furthermore, the negative electrode active material hard carbon, SP, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) were dissolved in deionized water in a stirring device at a mass ratio of 94:1:2:3, stirred evenly to form a slurry, coated on a 13 μm aluminum foil, and dried. After rolling and die-cutting, a negative electrode sheet was obtained.

[0054] (7) Cell preparation: The positive electrode sheet and the negative electrode sheet are stacked to obtain a roll core, which is packaged with an aluminum-plastic film and then baked in a vacuum nitrogen exchange process. When the moisture content reaches below 300 pm, the electrolyte is injected to seal the roll core. After high-temperature immersion for 48 hours, pressurized formation, high-temperature aging, capacity distribution, and K value testing, a 20Ah soft-pack sodium-ion battery is obtained.

[0055] Example 5

[0056] The positive electrode active material is a mixed material of composite sodium iron phosphate (NFPP) and metal layered oxide with a mass ratio of 0.5:9.5.

[0057] (1) Weighing raw materials: weighing according to the ratio of 95% active material, 2.5% binder, and 2.5% conductive agent, wherein the composite sodium iron phosphate accounts for 5% of the active material, wherein the conductive agent is conductive carbon black (SP), carbon nanotubes (CNTs) or a combination thereof, and the binder is polyvinylidene fluoride (PVDF), and the total weight of the powder is 8 kg.

[0058] (2) Preparation of adhesive solution: In an environment with humidity less than 10%, weigh 3298 g of solvent N-methylpyrrolidone (NMP) and add it to a stirring device, add 210.5 g of PVDF into the NMP and stir. The stirring device is kept in a vacuum state, the stirring revolution speed is 60 rpm, the dispersion speed is 3500 rpm, and the stirring time is 240 min to obtain PVDF adhesive solution.

[0059] (3) Preparation of conductive adhesive: SP and CNTs were added into PVDF adhesive solution, the stirring device was kept in vacuum state, the stirring revolution speed was 60 rpm, the dispersion speed was 3500 rpm, and the stirring time was 60 min to obtain PVDF adhesive solution.

[0060] (4) Preparation of slurry: The positive electrode active material is added to the conductive glue evenly three times and stirred. After scraping, the stirring equipment is kept in a vacuum state. The stirring revolution speed is 60 rpm, the dispersion speed is 4000 rpm, and the stirring time is 180 min. After adding solvent and stirring, the slurry viscosity is adjusted to 6000-8000 mPa.s and the fineness is less than 20 μm. After turning over to remove bubbles, it is coated.

[0061] (5) The obtained main material is coated on an aluminum foil with a thickness of 13 μm, and the NMP is removed by high-temperature drying in an oven. The mixed positive electrode sheet is obtained after rolling and die-cutting.

[0062] (6) Furthermore, the negative electrode active material hard carbon, SP, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) were dissolved in deionized water in a stirring device at a mass ratio of 94:1:2:3, stirred evenly to form a slurry, coated on a 13 μm aluminum foil, and dried. After rolling and die-cutting, a negative electrode sheet was obtained.

[0063] (7) Cell preparation: The positive electrode sheet and the negative electrode sheet are stacked to obtain a roll core, which is packaged with an aluminum-plastic film and then baked in a vacuum nitrogen exchange process. When the moisture content reaches below 300 pm, the electrolyte is injected to seal the roll core. After high-temperature immersion for 48 hours, pressurized formation, high-temperature aging, capacity distribution, and K value testing, a 20Ah soft-pack sodium-ion battery is obtained.

[0064] Example 6

[0065] The positive electrode active material is a mixed material of composite sodium iron phosphate (NFPP) and Prussian blue / white with a mass ratio of 3:7.

[0066] (1) Weighing the raw materials: weighing according to the ratio of 95% active material, 2.5% binder, and 2.5% conductive agent, wherein the composite sodium iron phosphate (NFPP) accounts for 30% of the active material, the conductive agent is conductive carbon black (SP), carbon nanotubes (CNTs) or a combination thereof, the binder is polyvinylidene fluoride (PVDF), and the total weight of the powder is 8 kg.

[0067] (2) Preparation of adhesive solution: In an environment with humidity less than 10%, weigh 3298 g of solvent N-methylpyrrolidone (NMP) and add it to a stirring device, add 210.5 g of PVDF into the NMP and stir. The stirring device is kept in a vacuum state, the stirring revolution speed is 60 rpm, the dispersion speed is 3500 rpm, and the stirring time is 240 min to obtain PVDF adhesive solution.

[0068] (3) Preparation of conductive adhesive: SP and CNTs were added into PVDF adhesive solution, the stirring device was kept in vacuum state, the stirring revolution speed was 60 rpm, the dispersion speed was 3500 rpm, and the stirring time was 60 min to obtain PVDF adhesive solution.

[0069] (4) Preparation of slurry: The positive electrode active material is added to the conductive glue evenly three times and stirred. After scraping, the stirring equipment is kept in a vacuum state. The stirring revolution speed is 60 rpm, the dispersion speed is 4000 rpm, and the stirring time is 180 min. After adding solvent and stirring, the slurry viscosity is adjusted to 6000-8000 mPa.s and the fineness is less than 20 μm. After turning over to remove bubbles, it is coated.

[0070] (5) The obtained main material is coated on an aluminum foil with a thickness of 13 μm, and the NMP is removed by high-temperature drying in an oven. The mixed positive electrode sheet is obtained after rolling and die-cutting.

[0071] (6) Furthermore, the negative electrode active material hard carbon, SP, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) were dissolved in deionized water in a stirring device at a mass ratio of 94:1:2:3, stirred evenly to form a slurry, coated on a 13 μm aluminum foil, and dried. After rolling and die-cutting, a negative electrode sheet was obtained.

[0072] (7) Cell preparation: The positive electrode sheet and the negative electrode sheet are stacked to obtain a roll core, which is packaged with an aluminum-plastic film and then baked in a vacuum nitrogen exchange process. When the moisture content reaches below 300 pm, the electrolyte is injected to seal the roll core. After high-temperature immersion for 48 hours, pressurized formation, high-temperature aging, capacity distribution, and K value testing, a 20Ah soft-pack sodium-ion battery is obtained.

[0073] Example 7

[0074] The positive electrode active material is a mixed material of composite sodium iron phosphate (NFPP) and Prussian blue / white with a mass ratio of 7:3.

[0075] (1) Weighing raw materials: weighing according to the ratio of 95% active material, 2.5% binder, and 2.5% conductive agent, wherein the composite sodium iron phosphate (NFPP) accounts for 70% of the active material, the conductive agent is conductive carbon black (SP), carbon nanotubes (CNTs) or a combination thereof, the binder is polyvinylidene fluoride (PVDF), and the total weight of the powder is 8 kg.

[0076] (2) Preparation of adhesive solution: In an environment with humidity less than 10%, weigh 3298 g of solvent N-methylpyrrolidone (NMP) and add it to a stirring device, add 210.5 g of PVDF into the NMP and stir. The stirring device is kept in a vacuum state, the stirring revolution speed is 60 rpm, the dispersion speed is 3500 rpm, and the stirring time is 240 min to obtain PVDF adhesive solution.

[0077] (3) Preparation of conductive adhesive: SP and CNTs were added into PVDF adhesive solution, the stirring device was kept in vacuum state, the stirring revolution speed was 60 rpm, the dispersion speed was 3500 rpm, and the stirring time was 60 min to obtain PVDF adhesive solution.

[0078] (4) Preparation of slurry: The positive electrode active material is added to the conductive glue evenly three times and stirred. After scraping, the stirring equipment is kept in a vacuum state. The stirring revolution speed is 60 rpm, the dispersion speed is 4000 rpm, and the stirring time is 180 min. After adding solvent and stirring, the slurry viscosity is adjusted to 6000-8000 mPa.s and the fineness is less than 20 μm. After turning over to remove bubbles, it is coated.

[0079] (5) The obtained main material is coated on an aluminum foil with a thickness of 13 μm, and the NMP is removed by high-temperature drying in an oven. The mixed positive electrode sheet is obtained after rolling and die-cutting.

[0080] (6) Furthermore, the negative electrode active material hard carbon, SP, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) were dissolved in deionized water in a stirring device at a mass ratio of 94:1:3:2, stirred evenly to form a slurry, coated on a 13 μm aluminum foil, and dried. After rolling and die-cutting, a negative electrode sheet was obtained.

[0081] (7) Cell preparation: The positive electrode sheet and the negative electrode sheet are stacked to obtain a roll core, which is packaged with an aluminum-plastic film and then baked in a vacuum nitrogen exchange process. When the moisture content reaches below 300 pm, the electrolyte is injected to seal the roll core. After high-temperature immersion for 48 hours, pressurized formation, high-temperature aging, capacity distribution, and K value testing, a 20Ah soft-pack sodium-ion battery is obtained.

[0082] Example 8

[0083] The positive electrode active material is a mixed material of composite sodium iron phosphate (NFPP) and sodium iron sulfate (NFS) with a mass ratio of 7:3.

[0084] (1) Weighing raw materials: weighing according to the ratio of 95% active material, 2.5% binder, and 2.5% conductive agent, wherein the composite sodium iron phosphate (NFPP) accounts for 70% of the active material, the conductive agent is conductive carbon black (SP), carbon nanotubes (CNTs) or a combination thereof, the binder is polyvinylidene fluoride (PVDF), and the total weight of the powder is 8 kg.

[0085] (2) Preparation of adhesive solution: In an environment with humidity less than 10%, weigh 3298 g of solvent N-methylpyrrolidone (NMP) and add it to a stirring device, add 210.5 g of PVDF into the NMP and stir. The stirring device is kept in a vacuum state, the stirring revolution speed is 60 rpm, the dispersion speed is 3500 rpm, and the stirring time is 240 min to obtain PVDF adhesive solution.

[0086] (3) Preparation of conductive adhesive: SP and CNsT were added to PVDF adhesive solution, the stirring equipment was kept in a vacuum state, the stirring revolution speed was 60 rpm, the dispersion speed was 3500 rpm, and the stirring time was 60 min to obtain PVDF adhesive solution.

[0087] (4) Preparation of slurry: The positive electrode active material is added to the conductive glue evenly three times and stirred. After scraping, the stirring equipment is kept in a vacuum state. The stirring revolution speed is 60 rpm, the dispersion speed is 4000 rpm, and the stirring time is 180 min. After adding solvent and stirring, the slurry viscosity is adjusted to 6000-8000 mPa.s and the fineness is less than 20 μm. After turning over to remove bubbles, it is coated.

[0088] (5) The obtained main material is coated on an aluminum foil with a thickness of 13 μm, and the NMP is removed by high-temperature drying in an oven. The mixed positive electrode sheet is obtained after rolling and die-cutting.

[0089] (6) Furthermore, the negative electrode active material hard carbon, SP, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) were dissolved in deionized water in a stirring device at a mass ratio of 94:1:2:3, stirred evenly to form a slurry, coated on a 13 μm aluminum foil, and dried. After rolling and die-cutting, a negative electrode sheet was obtained.

[0090] (7) Cell preparation: The positive electrode sheet and the negative electrode sheet are stacked to obtain a roll core, which is packaged with an aluminum-plastic film and then baked in a vacuum nitrogen exchange process. When the moisture content reaches below 300 pm, the electrolyte is injected to seal the roll core. After high-temperature immersion for 48 hours, pressurized formation, high-temperature aging, capacity distribution, and K value testing, a 20Ah soft-pack sodium-ion battery is obtained.

[0091] Example 9

[0092] The positive electrode active material is a mixed material of composite sodium iron phosphate (NFPP) and sodium iron sulfate (NFS) with a mass ratio of 3:7.

[0093] (1) Weighing the raw materials: weighing according to the ratio of 95% active material, 2.5% binder, and 2.5% conductive agent, wherein the composite sodium iron phosphate (NFPP) accounts for 30.0% of the active material, wherein the conductive agent is conductive carbon black (SP), carbon nanotubes (CNTs) or a combination thereof, and the binder is polyvinylidene fluoride (PVDF), and the total weight of the powder is 8 kg.

[0094] (2) Preparation of adhesive solution: In an environment with humidity less than 10%, weigh 3298 g of solvent N-methylpyrrolidone (NMP) and add it to a stirring device, add 210.5 g of PVDF into the NMP and stir. The stirring device is kept in a vacuum state, the stirring revolution speed is 60 rpm, the dispersion speed is 3500 rpm, and the stirring time is 240 min to obtain PVDF adhesive solution.

[0095] (3) Preparation of conductive adhesive: SP and CNTs were added into PVDF adhesive solution, the stirring device was kept in vacuum state, the stirring revolution speed was 60 rpm, the dispersion speed was 3500 rpm, and the stirring time was 60 min to obtain PVDF adhesive solution.

[0096] (4) Preparation of slurry: The positive electrode active material is added to the conductive glue evenly three times and stirred. After scraping, the stirring equipment is kept in a vacuum state. The stirring revolution speed is 60 rpm, the dispersion speed is 4000 rpm, and the stirring time is 180 min. After adding solvent and stirring, the slurry viscosity is adjusted to 6000-8000 mPa.s and the fineness is less than 20 μm. After turning over to remove bubbles, it is coated.

[0097] (5) The obtained main material is coated on an aluminum foil with a thickness of 13 μm, and the NMP is removed by high-temperature drying in an oven. The mixed positive electrode sheet is obtained after rolling and die-cutting.

[0098] (6) Furthermore, the negative electrode active material hard carbon, SP, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) were dissolved in deionized water in a stirring device at a mass ratio of 94:1:2:3, stirred evenly to form a slurry, coated on a 13 μm aluminum foil, and dried. After rolling and die-cutting, a negative electrode sheet was obtained.

[0099] (7) Cell preparation: The positive electrode sheet and the negative electrode sheet are stacked to obtain a roll core, which is packaged with an aluminum-plastic film and then baked in a vacuum nitrogen exchange process. When the moisture content reaches below 300 pm, the electrolyte is injected to seal the roll core. After high-temperature immersion for 48 hours, pressurized formation, high-temperature aging, capacity distribution, and K value testing, a 20Ah soft-pack sodium-ion battery is obtained.

[0100] Example 10

[0101] The positive electrode active material is a mixed material of composite sodium iron phosphate (NFPP), layered oxide, and Prussian blue / white in a mass ratio of 1:1:1.

[0102] (1) Weighing the raw materials: weighing according to the ratio of active material to binder to conductive agent to account for 95%, 2.5%, and 2.5%, wherein the composite sodium iron phosphate (NFPP) accounts for 33.33% of the active material, wherein the conductive agent is conductive carbon black (SP), carbon nanotubes (CNTs) or a combination thereof, and the binder is polyvinylidene fluoride (PVDF), and the total weight of the powder is 8 kg.

[0103] (2) Preparation of adhesive solution: In an environment with humidity less than 10%, weigh 3298 g of solvent N-methylpyrrolidone (NMP) and add it to a stirring device, add 210.5 g of PVDF into the NMP and stir. The stirring device is kept in a vacuum state, the stirring revolution speed is 60 rpm, the dispersion speed is 3500 rpm, and the stirring time is 240 min to obtain PVDF adhesive solution.

[0104] (3) Preparation of conductive adhesive: SP and CNsT were added to PVDF adhesive solution, the stirring equipment was kept in a vacuum state, the stirring revolution speed was 60 rpm, the dispersion speed was 3500 rpm, and the stirring time was 60 min to obtain PVDF adhesive solution.

[0105] (4) Preparation of slurry: The positive electrode active material is added to the conductive glue evenly three times and stirred. After scraping, the stirring equipment is kept in a vacuum state. The stirring revolution speed is 60 rpm, the dispersion speed is 4000 rpm, and the stirring time is 180 min. After adding solvent and stirring, the slurry viscosity is adjusted to 6000-8000 mPa.s and the fineness is less than 20 μm. After turning over to remove bubbles, it is coated.

[0106] (5) The obtained main material is coated on an aluminum foil with a thickness of 13 μm, and the NMP is removed by high-temperature drying in an oven. The mixed positive electrode sheet is obtained after rolling and die-cutting.

[0107] (6) Furthermore, the negative electrode active material hard carbon, SP, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) were dissolved in deionized water in a stirring device at a mass ratio of 94:1:2:3, stirred evenly to form a slurry, coated on a 13 μm aluminum foil, and dried. After rolling and die-cutting, a negative electrode sheet was obtained.

[0108] (7) Cell preparation: The positive electrode sheet and the negative electrode sheet are stacked to obtain a roll core, which is packaged with an aluminum-plastic film and then baked in a vacuum nitrogen exchange process. When the moisture content reaches below 300 pm, the electrolyte is injected to seal the roll core. After high-temperature immersion for 48 hours, pressurized formation, high-temperature aging, capacity distribution, and K value testing, a 20Ah soft-pack sodium-ion battery is obtained.

[0109] Embodiment 11

[0110] The positive electrode active material is a mixed material of composite sodium iron phosphate (NFPP), layered oxide and sodium iron sulfate (NFS) in a mass ratio of 1:1:1.

[0111] (1) Weighing the raw materials: weighing according to the ratio of active material to binder to conductive agent to account for 95%, 2.5%, and 2.5%, wherein the composite sodium iron phosphate (NFPP) accounts for 33.33% of the active material, wherein the conductive agent is conductive carbon black (SP), carbon nanotubes (CNTs) or a combination thereof, and the binder is polyvinylidene fluoride (PVDF), and the total weight of the powder is 8 kg.

[0112] (2) Preparation of adhesive solution: In an environment with humidity less than 10%, weigh 3298 g of solvent N-methylpyrrolidone (NMP) and add it to a stirring device, add 210.5 g of PVDF into the NMP and stir. The stirring device is kept in a vacuum state, the stirring revolution speed is 60 rpm, the dispersion speed is 3500 rpm, and the stirring time is 240 min to obtain PVDF adhesive solution.

[0113] (3) Preparation of conductive adhesive: SP and CNTs were added into PVDF adhesive solution, the stirring device was kept in vacuum state, the stirring revolution speed was 60 rpm, the dispersion speed was 3500 rpm, and the stirring time was 60 min to obtain PVDF adhesive solution.

[0114] (4) Preparation of slurry: The positive electrode active material is added to the conductive glue evenly three times and stirred. After scraping, the stirring equipment is kept in a vacuum state. The stirring revolution speed is 60 rpm, the dispersion speed is 4000 rpm, and the stirring time is 180 min. After adding solvent and stirring, the slurry viscosity is adjusted to 6000-8000 mPa.s and the fineness is less than 20 μm. After turning over to remove bubbles, it is coated.

[0115] (5) The obtained main material is coated on an aluminum foil with a thickness of 13 μm, and the NMP is removed by high-temperature drying in an oven. The mixed positive electrode sheet is obtained after rolling and die-cutting.

[0116] (6) Furthermore, the negative electrode active material hard carbon, SP, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) were dissolved in deionized water in a stirring device at a mass ratio of 94:1:3:2, stirred evenly to form a slurry, coated on a 13 μm aluminum foil, and dried. After rolling and die-cutting, a negative electrode sheet was obtained.

[0117] (7) Cell preparation: The positive electrode sheet and the negative electrode sheet are stacked to obtain a roll core, which is packaged with an aluminum-plastic film and then baked in a vacuum nitrogen exchange process. When the moisture content reaches below 300 pm, the electrolyte is injected to seal the roll core. After high-temperature immersion for 48 hours, pressurized formation, high-temperature aging, capacity distribution, and K value testing, a 20Ah soft-pack sodium-ion battery is obtained.

[0118] Example 12

[0119] The positive electrode active material is a mixed material of composite sodium iron phosphate (NFPP), sodium iron sulfate (NFS), layered oxide, and Prussian blue / white in a mass ratio of 1:1:1:1.

[0120] (1) Weighing raw materials: weighing according to the ratio of active material to binder to conductive agent to account for 95%, 2.5%, and 2.5%, wherein the composite sodium iron phosphate (NFPP) accounts for 25% of the active material, wherein the conductive agent is conductive carbon black (SP), carbon nanotubes (CNTs) or a combination thereof, and the binder is polyvinylidene fluoride (PVDF), and the total weight of the powder is 8 kg.

[0121] (2) Preparation of adhesive solution: In an environment with humidity less than 10%, weigh 3298 g of solvent N-methylpyrrolidone (NMP) and add it to a stirring device, add 210.5 g of PVDF into the NMP and stir. The stirring device is kept in a vacuum state, the stirring revolution speed is 60 rpm, the dispersion speed is 3500 rpm, and the stirring time is 240 min to obtain PVDF adhesive solution.

[0122] (3) Preparation of conductive adhesive: SP and CNTs were added into PVDF adhesive solution, the stirring device was kept in vacuum state, the stirring revolution speed was 60 rpm, the dispersion speed was 3500 rpm, and the stirring time was 60 min to obtain PVDF adhesive solution.

[0123] (4) Preparation of slurry: The positive electrode active material is added to the conductive glue evenly three times and stirred. After scraping, the stirring equipment is kept in a vacuum state. The stirring revolution speed is 60 rpm, the dispersion speed is 4000 rpm, and the stirring time is 180 min. After adding solvent and stirring, the slurry viscosity is adjusted to 6000-8000 mPa.s and the fineness is less than 20 μm. After turning over to remove bubbles, it is coated.

[0124] (5) The obtained main material is coated on an aluminum foil with a thickness of 13 μm, and the NMP is removed by high-temperature drying in an oven. The mixed positive electrode sheet is obtained after rolling and die-cutting.

[0125] (6) Furthermore, the negative electrode active material hard carbon, SP, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) were dissolved in deionized water in a stirring device at a mass ratio of 94:1:2:3, stirred evenly to form a slurry, coated on a 13 μm aluminum foil, and dried. After rolling and die-cutting, a negative electrode sheet was obtained.

[0126] (7) Cell preparation: The positive electrode sheet and the negative electrode sheet are stacked to obtain a roll core, which is packaged with an aluminum-plastic film and then baked in a vacuum nitrogen exchange process. When the moisture content reaches below 300 pm, the electrolyte is injected to seal the roll core. After high-temperature immersion for 48 hours, pressurized formation, high-temperature aging, capacity distribution, and K value testing, a 20Ah soft-pack sodium-ion battery is obtained.

[0127] Comparative Example 1

[0128] The positive electrode active material is a layered metal oxide.

[0129] (1) Weighing raw materials: weighing according to the ratio of 95% active material, 2.5% binder, and 2.5% conductive agent, wherein the active material is a layered metal oxide, the conductive agent is conductive carbon black (SP), carbon nanotubes (CNTs) or a combination thereof, the binder is polyvinylidene fluoride (PVDF), and the total weight of the powder is 8 kg.

[0130] (2) Preparation of adhesive solution: In an environment with humidity less than 10%, weigh 3298 g of solvent N-methylpyrrolidone (NMP) and add it to a stirring device, add 210.5 g of PVDF into the NMP and stir. The stirring device is kept in a vacuum state, the stirring revolution speed is 60 rpm, the dispersion speed is 3500 rpm, and the stirring time is 240 min to obtain PVDF adhesive solution.

[0131] (3) Preparation of conductive adhesive: SP and CNTs were added into PVDF adhesive solution, the stirring device was kept in vacuum state, the stirring revolution speed was 60 rpm, the dispersion speed was 3500 rpm, and the stirring time was 60 min to obtain PVDF adhesive solution.

[0132] (4) Preparation of slurry: The positive electrode active material is added to the conductive glue evenly three times and stirred. After scraping, the stirring equipment is kept in a vacuum state. The stirring revolution speed is 60 rpm, the dispersion speed is 4000 rpm, and the stirring time is 180 min. After adding solvent and stirring, the slurry viscosity is adjusted to 6000-8000 mPa.s and the fineness is less than 20 μm. After turning over to remove bubbles, it is coated.

[0133] (5) The obtained main material is coated on an aluminum foil with a thickness of 13 μm, and the NMP is removed by high-temperature drying in an oven. The mixed positive electrode sheet is obtained after rolling and die-cutting.

[0134] (6) Furthermore, the negative electrode active material hard carbon, SP, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) were dissolved in deionized water in a stirring device at a mass ratio of 94:1:2:3, stirred evenly to form a slurry, coated on a 13 μm aluminum foil, and dried. After rolling and die-cutting, a negative electrode sheet was obtained.

[0135] (7) Cell preparation: The positive electrode sheet and the negative electrode sheet are stacked to obtain a roll core, which is packaged with an aluminum-plastic film and then baked in a vacuum nitrogen exchange process. When the moisture content reaches below 300 pm, the electrolyte is injected to seal the roll core. After high-temperature immersion for 48 hours, pressurized formation, high-temperature aging, capacity distribution, and K value testing, a 20Ah soft-pack sodium-ion battery is obtained.

[0136] Comparative Example 2

[0137] The positive electrode active material is composite sodium iron phosphate (NFPP)

[0138] (1) Weighing raw materials: weighing according to the ratio of 95% active material, 2.5% binder, and 2.5% conductive agent, wherein the active material is a layered metal oxide, the conductive agent is conductive carbon black (SP), carbon nanotubes (CNTs) or a combination thereof, the binder is polyvinylidene fluoride (PVDF), and the total weight of the powder is 8 kg.

[0139] (2) Preparation of adhesive solution: In an environment with humidity less than 10%, weigh 3298 g of solvent N-methylpyrrolidone (NMP) and add it to a stirring device, add 210.5 g of PVDF into the NMP and stir. The stirring device is kept in a vacuum state, the stirring revolution speed is 60 rpm, the dispersion speed is 3500 rpm, and the stirring time is 240 min to obtain PVDF adhesive solution.

[0140] (3) Preparation of conductive adhesive: SP and CNTs were added into PVDF adhesive solution, the stirring device was kept in vacuum state, the stirring revolution speed was 60 rpm, the dispersion speed was 3500 rpm, and the stirring time was 60 min to obtain PVDF adhesive solution.

[0141] (4) Preparation of slurry: The positive electrode active material is added to the conductive glue evenly three times and stirred. After scraping, the stirring equipment is kept in a vacuum state. The stirring revolution speed is 60 rpm, the dispersion speed is 4000 rpm, and the stirring time is 180 min. After adding solvent and stirring, the slurry viscosity is adjusted to 6000-8000 mPa.s and the fineness is less than 20 μm. After turning over to remove bubbles, it is coated.

[0142] (5) The obtained main material is coated on an aluminum foil with a thickness of 13 μm, and the NMP is removed by high-temperature drying in an oven. The mixed positive electrode sheet is obtained after rolling and die-cutting.

[0143] (6) Furthermore, the negative electrode active material hard carbon, SP, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) were dissolved in deionized water in a stirring device at a mass ratio of 94:1:2:3, stirred evenly to form a slurry, coated on a 13 μm aluminum foil, and dried. After rolling and die-cutting, a negative electrode sheet was obtained.

[0144] (7) Cell preparation: The positive electrode sheet and the negative electrode sheet are stacked to obtain a roll core, which is packaged with an aluminum-plastic film and then baked in a vacuum nitrogen exchange process. When the moisture content reaches below 300 pm, the electrolyte is injected to seal the roll core. After high-temperature immersion for 48 hours, pressurized formation, high-temperature aging, capacity distribution, and K value testing, a 20Ah soft-pack sodium-ion battery is obtained.

[0145] The soft-pack batteries prepared in Examples 1, 2, 3, 4 and Comparative Example 1 were tested for safety performance such as needle puncture and overcharging. The safety performance of the soft-pack batteries prepared in Examples 1, 2, 3, and 4 was better than that of Comparative Example 1. Examples 1, 2, 3, and 4 did not catch fire or explode, while the comparative example caught fire (see Table 1).

[0146] The soft-pack batteries prepared in Examples 1 to 15 and Comparative Example 2 were subjected to electrical performance tests and the energy density of the battery cells was calculated. The energy density of the soft-pack batteries prepared in Examples 1 to 15 was greater than that of Comparative Example 2.

[0147] The soft-pack batteries prepared in Examples 1, 2, 3 and Comparative Example 1 were tested for cycle performance.

[0148] The cycle performance of Examples 1, 2, and 3 is better than that of Comparative Example 1 (see Figure 1 ).

[0149] For test methods and test result standards, please refer to GB / T-31485-2015.

[0150] Test items acupuncture Overcharge Example 1 No fire, no explosion, passed the test No fire, no explosion, passed the test Example 2 No fire, no explosion, passed the test No fire, no explosion, passed the test Example 3 No fire, no explosion, passed the test No fire, no explosion, passed the test Example 4 No fire, no explosion, passed the test No fire, no explosion, passed the test Comparative Example 1 Fire, failed the test Fire, failed the test

[0151] Table 1

[0152] The above examples are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A sodium ion battery positive electrode material active substance mixed with composite sodium iron phosphate, characterized in that: The active substance of the sodium ion battery positive electrode material is a mixture of composite sodium iron phosphate (NFPP) and one or more of layered metal oxides, Prussian blue compounds, and other polyanion materials, wherein the composite sodium iron phosphate (NFPP) accounts for 5% to 95% of the active substance of the sodium ion battery positive electrode material, and the other 95% to 5% is a material obtained by mixing one or more of layered metal oxides, Prussian blue compounds, and other polyanion materials.

2. A sodium ion battery positive electrode material mixed with composite sodium iron phosphate, characterized in that: The invention comprises the sodium ion battery positive electrode material active substance, a conductive agent and a binder as claimed in claim 1; the sodium ion battery positive electrode material active substance accounts for 93% to 97%, the binder accounts for 1.5% to 3.5%, and the conductive agent accounts for 1% to 3.5%.

3. The sodium ion positive electrode material according to claim 2, characterized in that: The binder is polyvinylidene fluoride (PVDF); the conductive agent is any one of conductive carbon black (SP), conductive graphite, acetylene black, carbon nanotubes (CNTs), or a composite conductive agent mixed with any of the above.

4. The sodium ion positive electrode material according to claim 2, characterized in that: The solvent for preparing the sodium ion positive electrode material is N-methylpyrrolidone (NMP).

5. A sodium ion battery, characterized in that: The invention comprises a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode is a positive electrode sheet prepared from the sodium ion positive electrode material according to claims 2 to 4.

6. The sodium ion battery according to claim 5, characterized in that The sodium ion battery adopts a cylindrical battery cell, a soft-pack battery cell or a square-shell battery cell.

7. The sodium ion battery according to claim 5, characterized in that: The negative electrode is hard carbon.

8. The sodium ion battery according to claim 5, characterized in that: The electrolyte of the electrolyte is one or both of NaPF6 and NaFSI.

Citation Information

Cited By

  • Sodium ferric phosphate pyrophosphate material of high-voltage platform, positive pole piece, battery cell and preparation method of sodium ferric phosphate pyrophosphate material

    CN120600794A